Avaliação sobre o comportamento de antimicrobianos veterinários em solo e em cama de frango: estudos de adsorção e previsão do potencial de contaminação de águas superficiais e subterrâneas - Toledo Netto, Pedro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Veterinary antimicrobials are widely used in the poultry production for disease prevention and growth promotion. It is estimated that for some of them, up to 90 % of the administered dose is eliminated in its unmetabolized form or as active metabolites. Therefore, large amounts of these substances are released into the environment, whose impacts caused by its dispersion can reach large proportions, contaminating surface and groundwater, air, soil, plants, threatening aquatic and terrestrial organisms and spreading of resistant bacteria. However, data about the occurrence and behavior of veterinary antimicrobials in the environment are very limited in Brazil. Therefore, the objectives of this work were: (i) to evaluate the adsorption nine veterinary antimicrobials (amoxicillin, lincomycin, tylosin, trimethoprim, sulfadiazine, oxytetracycline, ciprofloxacin, enrofloxacin, and norfloxacin) in soil and peat of the State of São Paulo using different treatments and in poultry litter associated to soil; (ii) to propose adsorption models that best represents this process; (iii) to estimate the potential for contamination of surface and groundwater using the normalized adsorption coefficients (Koc) obtained in this study. The determination of the compounds was performed using high performance liquid chromatography with ultraviolet and fluorescence detectors, with good chromatographic resolution and suitable quantification limits. For antimicrobials analyzed individually in soil, the adsorption linear model was satisfactory with correlation coefficients ranging between 0,844 and 0,983. Although the adsorption models applied were not appropriate for the mixture antimicrobials adsorption for the soil and soil associated to poultry litter, these factors caused a decrease of adsorption for most antimicrobials studied in all concentration levels evaluated, except for amoxicillin that showed opposite effect. The calcination of soil and peat was...

Antimicrobianos veterinários são muito utilizados na criação de frangos de corte para prevenção de doenças e promoção de crescimento. Estima-se que para alguns deles, até 90% da dose administrada seja eliminada em sua forma não metabolizada ou como metabólitos ativos. Portanto, elevadas quantidades destas substâncias são lançadas no meio ambiente, cujos impactos causados por sua dispersão podem alcançar grandes proporções, contaminando águas superficiais e subterrâneas, ar, solos, plantas, ameaçando organismos terrestres e aquáticos e a disseminação de bactérias resistentes. Entretanto, dados relativos sobre a ocorrência e comportamentos de antimicrobianos veterinários no meio ambiente são muito escassos no Brasil. Portanto, os objetivos deste trabalho foram: (i) avaliar a adsorção de nove antimicrobianos veterinários (amoxicilina, lincomicina, tilosina, trimetropina, sulfadiazina, oxitetraciclina, ciprofloxacina, enrofloxacina e norfloxacina) em solo e turfa do Estado de São Paulo e em cama de frango associada ao solo; (ii) propor modelos de adsorção que melhor se ajustam a este fenômeno; (iii) realizar previsão do potencial de contaminação de águas superficiais e subterrâneas. A determinação dos compostos foi realizada utilizando a cromatografia líquida de alta eficiência com detectores de ultravioleta e fluorescência, apresentando resolução cromatográfica e limites de quantificação adequados. Para os antimicrobianos determinados individualmente no solo, o modelo de adsorção linear foi mais satisfatório com coeficientes de correlação situados entre 0,844 e 0,983. Embora os modelos de adsorção aplicados não tenham sido adequados ao processo de adsorção dos antimicrobianos em mistura, tanto no solo quanto na cama de frango associada ao solo, foi possível indicar que estes fatores provocam diminuição da adsorção para a maioria dos antimicrobianos estudados em todos os níveis de...
Keywords: Quimica analitica; Agentes antiinfecciosos; Solos; Contaminação; Adsorção; Soil